Правове виховання особистості дитини: поняття, сутність, особливості - Задорожна, Ганна (My University, 2017)
У статті розглядається й уточнюється сутність понять: «громадянське виховання», «правове виховання», «моральне виховання», які здійснюються як цілісний педагогічний процес організації життя дітей: діяльності, стосунків, спілкування з урахуванням вікових та індивідуальних особливостей у період дошкільного та молодшого шкільного віку. Визначено триєдину мету правового виховання та особливості правового виховання дітей 6-7-років в аспекті наступності та перспективності. The article is devoted to the analysis and distinguishing of concepts’ essence: «civic education», «legal education», «moral education», which are implemented as a holistic pedagogical process of organizing the life of children: activities, relationships, communication with age and individual characteristics in the period of preschool and junior school age. The three goals of the legal education of children are formulated: 1) the formation of ideas about rights and laws, increase of their legal literacy, understanding of the necessity of observance of the norms of these laws, which will promote the development of self-esteem, respect for oneself, their parents, to other people, the formation of the correct "legal "Communication with other children, the ability to protect themselves from a legal position; 2) the formation of legal consciousness as a set of legal representations, views, beliefs, feelings that determine the attitude of the individual to the requirements of laws and regulate behavior in a particular legal situation; 3) the formation of lawful conduct, negative attitude to the facts of offenses and crimes, which will allow the child to analyze their own actions and behavior of other children and adults in the context of observance of their generally accepted norms and rules, as well as legislative requirements. The peculiarities of legal education of children 6-7 years in the aspect of continuity and perspective are determined.
Keywords: правове виховання; громадянське виховання; моральне виховання; дошкільний вік; молодший шкільний вік; наступність; перспективність